New strategies for targeting the hypoxic tumour microenvironment in breast cancer. - Ward, C; Langdon, S; Mullen, P; Harris, A; Harrison, D; Supuran, C; Kunkler, I (2013)
Radiation and drug resistance remain major challenges and causes of mortality in the treatment of locally advanced, recurrent and metastatic breast cancer. Metabolic reprogramming is a recently recognised hallmark of cancer with the hypoxic acidic extracellular environment as a major driver of invasion and metastases. Nearly 40% of all breast cancers and 50% of locally advanced breast cancers are hypoxic and their altered metabolism is strongly linked to resistance to radiotherapy and systemic therapy. The dependence of metabolically adapted breast cancer cells on alterations in cell function presents a wide range of new therapeutic targets such as carbonic anhydrase IX (CAIX). This review highlights preclinical approaches to evaluating an array of targets against tumour metabolism in breast cancer and early phase clinical studies on efficacy.